2023
DOI: 10.3390/cimb45030168
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Diet Enriched with Jerusalem artichoke, Inulin, and Fluoxetine on Cognitive Functions, Neurogenesis, and the Composition of the Intestinal Microbiota in Mice

Abstract: The aim of the study was to assess the effect of long-term administration of natural prebiotics: Jerusalem artichoke (topinambur, TPB) and inulin (INU) as well as one of the most popular antidepressants, fluoxetine (FLU), on the proliferation of neural stem cells, learning and memory functions, and the composition of the intestinal microbiota in mice. Cognitive functions were assessed using the Morris Water Maze (MWM)Test. Cells were counted using a confocal microscope and ImageJ software. We performed 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 87 publications
0
0
0
Order By: Relevance
“…All study groups showed significantly better time and distance to reach the platform compared to the Control CUMS mice. MWM results from our previous studies evaluating the effect of a 10-week diet of TPB (250 mg/kg) and INU (66 mg/kg) on healthy mice showed no statistically significant differences in the time and distance needed to find the platform in comparison to a healthy control mice, whereas FLU (12 mg/kg) significantly disturbed the time and distance parameters [30]. Similar results confirming the beneficial effect of inulin on cognitive functions were presented by Messaoudi et al [54] investigating the effectiveness of oral administration of oligofructose enriched inulin at doses of 5 and 10% on the behavior and cognition of male Wistar rats.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…All study groups showed significantly better time and distance to reach the platform compared to the Control CUMS mice. MWM results from our previous studies evaluating the effect of a 10-week diet of TPB (250 mg/kg) and INU (66 mg/kg) on healthy mice showed no statistically significant differences in the time and distance needed to find the platform in comparison to a healthy control mice, whereas FLU (12 mg/kg) significantly disturbed the time and distance parameters [30]. Similar results confirming the beneficial effect of inulin on cognitive functions were presented by Messaoudi et al [54] investigating the effectiveness of oral administration of oligofructose enriched inulin at doses of 5 and 10% on the behavior and cognition of male Wistar rats.…”
Section: Discussionmentioning
confidence: 76%
“…Our neurogenesis study results indicated strong protective properties of TPB and INU preventive supplementation on the stem cell proliferation compared to Control CUMS mice, whereas FLU administration slightly increased BrDU+ cells in the tested FLU CUMS group. Our previous results concerning TPB and INU supplementation on healthy mice indicated no changes in BrDU+ cells, whereas 2 weeks administration of FLU (12 mg/kg) statistically significantly reduced the number of BrDU+ cells compared to the healthy control group [30]. Similarly, David et al [55] evaluated the effect of a 3-week treatment with FLU in a model of anxiety and depression caused by over-exposure to glucocorticoids in C57BL/6Ntac mice.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations